The role of visualization: a study of the effectiveness of commercial photograph in advertising field - Loke, Hon Leong (2011)
Commercial photographs appears anywhere, it creates a strong relationship in our daily life. Advertisers will use photographs to representing the brand image and convey the messages for the promotions. It become an important tools is advertising. This study will focus to the functions of commercial photographs in advertising, the objective of the study are to clarify the importance and effectiveness of commercial photographs. This study will revealed about the importance of visual literacy and visual metaphor towards the photographs and it also investigates the relationship between the commercial photographs and consumers. A sample of hundred (100) randomly, age fifteen (15) to fifty-four (54) consumers as target group where else in-depth interviewees involve twelve (12) people in two (2) categories which are professional staff and audiences. The finding and conclusions will signify the function of the visual images and how the audiences are react to the commercial photographs in advertisements.